2008
DOI: 10.1093/jac/dkn396
|View full text |Cite
|
Sign up to set email alerts
|

Arrival of Klebsiella pneumoniae producing KPC carbapenemase in the United Kingdom

Abstract: The first KPC-3-producing K. pneumoniae isolates detected in the UK were highly genetically related to a KPC-3-producing Israeli K. pneumoniae strain. This relatedness was consistent with the history of one UK patient, who had been hospitalized previously in Israel. However, this strain may be circulating more widely since the second UK patient had no identifiable links with Israel or other overseas countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
89
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 14 publications
2
89
0
5
Order By: Relevance
“…Heteroresistant colonies had significantly elevated expression of the bla KPC gene compared with the native populations but did not retain heteroresistance when subcultured in drug-free media. Time-kill assays indicated that meropenem alone was not bactericidal against KPC-KP but efficiently killed the control strains.Since the beginning of the last decade, Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae (KPC-KP) isolates have been increasingly detected in the United States and subsequently in several regions worldwide (3,4,13,17,21). KPC enzymes efficiently hydrolyze all ␤-lactam molecules (1, 22), conferring various levels of resistance to all ␤-lactam compounds, including carbapenems (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Heteroresistant colonies had significantly elevated expression of the bla KPC gene compared with the native populations but did not retain heteroresistance when subcultured in drug-free media. Time-kill assays indicated that meropenem alone was not bactericidal against KPC-KP but efficiently killed the control strains.Since the beginning of the last decade, Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae (KPC-KP) isolates have been increasingly detected in the United States and subsequently in several regions worldwide (3,4,13,17,21). KPC enzymes efficiently hydrolyze all ␤-lactam molecules (1, 22), conferring various levels of resistance to all ␤-lactam compounds, including carbapenems (13).…”
mentioning
confidence: 99%
“…Since the beginning of the last decade, Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae (KPC-KP) isolates have been increasingly detected in the United States and subsequently in several regions worldwide (3,4,13,17,21). KPC enzymes efficiently hydrolyze all ␤-lactam molecules (1, 22), conferring various levels of resistance to all ␤-lactam compounds, including carbapenems (13).…”
mentioning
confidence: 99%
“…Estas observaciones coinciden con la situación mundial, en la que se evidencia que los carbapenémicos ven comprometida su efectividad por la diseminación de carbapenemasas de tipo KPC (53). Las alternativas terapéuticas se han visto reducidas a productos de menor eficacia, o sobre los cuales hay menor información, como la tigeciclina y la colistina, aunque en algunas cepas también se ha detectado el surgimiento de resistencia a estos antibióticos (67,68). Otro problema ya conocido es la resistencia mediada por betalactamasas de la variante AmpC con expresión cromosómica natural en Enterobacter spp., y la aparición de variantes AmpC mutantes capaces de elevados niveles de producción, lo que explicaría en parte el aumento observado en la resistencia de E. cloacae al meropenem en los últimos años.…”
Section: Discussionunclassified
“…The target DNA used for the hybridization onto the oligonucleotide microarrays was synthesized via PCR. The primers used for the amplification of the bla KPC gene were the forward primer KPC_PR_F1 (5=-TGTCACTGTATCGCCGTG-3=) (48) and the reverse primer KPC_PR_R2 (5=-TTGACGCCCAATCCCT-3=), developed as part of this study. The amplicon was expected to be 871 bp in length.…”
Section: Methodsmentioning
confidence: 99%